Importance of employer-employee relationship towards the growth of a business - Hannis Ansah, R.; Osei, Jane; Sorooshian, Shahryar; Aikhuele, Daniel Osezua (Romanian Society for Quality Assurance - SRAC, 2018)
Most often, employer-employee relationships may contribute to the achievement of organizational goals or otherwise. The type of relationship built in an organization may affect productivity negatively or positively. Though the objective of every organization is to maximize profit, employer-employee relationship can be a hindrance to the achievement of those objectives. The objective of this research is to present evidence-based information to readers on the importance of the employer-employee relationship towards the growth of a business. The paper also highlights the role of job satisfaction towards inspiring good relationships between these two parties and recommends guidelines on how the relationship can be managed. To extend the qualitative data, a relationship survey was designed to assess Ghanaian business owners and employees' opinions about relationships, and its significant role towards the success of their businesses. Also, the survey measured job satisfaction of the employees. From the results, job satisfaction was identified as the accurate indicator of good relationships between employers and employees. The study found that business owners shared a positive notion that relationships play an important role towards their business as these contribute to the growth of their business.